Sensors, Actuators, and their Interfaces : a Multidisciplinary Introduction - Ida, Nathan (SciTech Publishing Inc., 2014)
The book has 12 chapters dealing with the following topics: performance characteristics of sensors and actuators; temperature sensors and thermal actuators; optical sensors and actuators; electric and magnetic sensors; mechanical sensors; acoustic sensors; chemical sensors; radiation sensors; MEMS and smart sensors; microprocessors; interfacing methods and circuits.
Keywords: Actuators.; Chemical detectors.; Micromechanics.; Microprocessors.; elektronické knihy; electronic books